Ten-Year Outcomes of Intravitreal Bevacizumab for Myopic Choroidal Neovascularization: Analysis of Prognostic Factors - Fabiana Mallone; Rosalia Giustolisi; Federica Franzone; Marco Marenco; Rocco Plateroti; Marcella Nebbioso; Alessandro Lambiase; Magda Gharbiya (MDPI AG, 2021)
The current standard treatment of myopic choroidal neovascularisation (mCNV) is intravitreal injection of VEGF antagonists. This study was proposed to assess efficacy and safety of intravitreal bevacizumab (IVB) for the treatment of mCNV across a 10-year follow-up. Thirty eyes of thirty patients with treatment-naïve mCNV who underwent IVB and were followed up with for a minimum of ten years were recruited for the present retrospective cohort study. All participants were treated with three monthly IVB at baseline and then evaluated and treated under pro re nata (PRN) schedule. Outcome measures were to determine BCVA changes over years and identify the predictive factors of both final visual outcome and need for retreatment. Analysis of the main involved prognostic factors with correlations among variables is reported. Visual acuity remained stable at 10-year follow-up (p = 0.001) with the greatest improvement at 2 years (p < 0.0001) in all CNV locations. Baseline BCVA correlated positively with final BCVA (β = 0.88, p < 0.0001, R2: 0.75). No predictive factors for the need of additional injections were identified. Retinal and choroidal thickness significantly reduced over time but without correlation with the number of injections. CNV max height and area significantly decreased at 10 years (p < 0.0001 and p = 0.003, respectively), with complete regression of mCNV lesion in 40% of subjects. Intravitreal bevacizumab resulted as long-term effective and safe therapy for mCNV with sustained results at 10 years.